Analyzing Madhesh Movement from a Social Structural Approach - Subedi, Tek Nath (Journal of Development Review, 2023)
Collective human activities are the motors of social change. Change depends less on mutual understanding and more on the contradiction between different micro-to-macro-level functioning units. Thus, sociological theories bring together the network of relationship between manifold social layers while analyzing the status of continuity or flux of change in society. Insofar as Nepali society has undergone tremendous changes, attempts of inserting more recent sociological theories becomes customary. Contrary to this, the application of classical theories in analyzing the socio-political transformations has been a usual trend. The 2007-Madhesh Movement was one of the major turning points in Nepal’s socio-political history, which had brought significant macro-level changes in Nepal. Several scholarly attempts are made to discuss and analyze the Movement, but emphasis is given more to the internal structure bypassing the international structure. This paper aims to analyze the Madhesh Movement with reference to an acclaimed book ‘Madhesh Bidrohako Nalibeli’, and examines whether the book has applied the most updated sociological theories of social movement such as Theda Skocpol’s social structural approach. The book is found too slim in defining and theorizing the movement sociologically since it has given credit only to national-level phenomena than the global capitalist process. This paper confirms that the proper positioning of macro-level structural contexts and the development at home and abroad can help anyone better understand the movement.